Applications of bioflocculants for heavy metals removal: a systematic review - Yang, Wang; Pushiri, Hafizah; Ley, Juen Looi; Zulkeflee, Zufarzaana (University of Tehran, 2022)
Heavy metals from various natural and anthropogenic processes have become a main threat to the aquatic environment owing to their hazardous impact. Bioflocculant is a natural organic polymer that is produced by microbes with flocculating capabilities. Compared to chemical flocculants, they are safer, biodegradable, and inexpensive. For decades, a diverse range of bioflocculant has been tested for their ability to remove heavy metals. This review is performed to gather the findings from December 2011 to June 2021 on bioflocculant produced by different bacterial species and their capabilities to remove heavy metals with different influencing factors. Based on defined inclusion criteria including bioflocculant treatment of metals in wastewater and aquatic environments, 35 studies were chosen to be included in this review. The results demonstrated that various microbial species, namely Pseudomonas sp., Bacillus sp., Paenibacillus sp., Pantoea sp., Proteus sp., Stenotrophomonas sp., Herbaspirillium sp., Halomonas sp., Achromobacter sp., Nocardiopsis sp., Turicibacter sp., Raoultella sp., and mixed bacteria (Cloacibacterium sp., and Rhizobium sp.) have the capability for heavy metal removal through bioflocculation. Important factors influencing heavy metal removal efficiencies among the bacteria include self-microbial properties, pH, bioflocculant dosage, metal concentration, contact time, and temperature. These findings outline the best available options for the utilization of bioflocculant to remove heavy metals in water treatment industries.